Arts of living : reinventing the humanities for the twenty-first century - Spellmeyer, Kurt (State University of New York Press, 2003)
"Arts of Living presents a social history of the humanities and a proposal for the future that places creativity at the heart of higher education. Engaging with the debate launched by Allan Bloom, Harold Bloom, Bill Readings, John Guillory, and others, Kurt Spellmeyer argues that higher education needs to abandon the "culture wars" if it hopes to address the major crises of the century: globalization, the degradation of the environment, the widening chasm between rich and poor, and the clash of cultures."--Jacket